2020
DOI: 10.1016/j.ijbiomac.2020.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Films of chitosan and natural modified hydroxyapatite as effective UV-protecting, biocompatible and antibacterial wound dressings

Abstract: Chitosan is a natural polysaccharide widely used in biomedicine, for instance for wound dressing. Hydroxyapatite is a very bioactive calcium phosphate which, if modified with an appropriate element (iron Fe), can also have UVabsorbing properties. In this work, we report the study of films of chitosan incorporated with iron-modified hydroxyapatite of natural origin (from cod fish bones); this combination led to an innovative chitosan-based material with excellent and advanced functional properties. The films sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…There are numerous similarities between CS and the native glycosaminoglycans’ structure, which improves the rate of bone regeneration. Thus, Cunha et al noted that amino and hydroxyl functional groups enable chemical modifications, increasing the potential of CS-based nanocomposites, which have gained significant attention in this domain [ 39 , 40 ]. Such an application can be seen in Figure 2 , illustrating the inhibition phenomenon of bacterial attachment.…”
Section: Polymers Applied In Btementioning
confidence: 99%
“…There are numerous similarities between CS and the native glycosaminoglycans’ structure, which improves the rate of bone regeneration. Thus, Cunha et al noted that amino and hydroxyl functional groups enable chemical modifications, increasing the potential of CS-based nanocomposites, which have gained significant attention in this domain [ 39 , 40 ]. Such an application can be seen in Figure 2 , illustrating the inhibition phenomenon of bacterial attachment.…”
Section: Polymers Applied In Btementioning
confidence: 99%
“…In recent years, HA has been proposed as a safe sunscreen ingredient, and the interest in CaPs for this application is growing [195,196]. In the literature, there are several examples that report the preparation of HA as a safe inorganic sunscreen ingredient to replace ZnO and TiO 2 [197][198][199][200][201][202][203][204][205][206][207][208][209][210][211]. Indeed, it was found that HA shows not only non-toxicity and biocompatibility properties, but also screening capability, high dermal tolerance, and a lower whitening effect than other inorganic sunscreen agents.…”
Section: Skin Protection-sunscreen (Uv Protection)mentioning
confidence: 99%
“…They noticed excellent UV-absorbing properties, antibacterial activity, and non-cytotoxicity. This material could be used for wound dressing, because it reduces bacterial infection while protecting wounds from UV exposure [205]. Another example is the work of Ghazali et al, which reports the preparation of an active sunscreen ingredient from clamshells by substituting calcium ions of HA structure with Fe 3+ or Mn 2+ [210].…”
Section: Natural Calcium Phosphates As Sunscreensmentioning
confidence: 99%
“…These coating materials can be in form of hydrogels, films or delivery systems deposited on support materials, their main characteristic being a good compatibility between the components and the active substances [52]. For the development of a proper coating material, various aspects need to be considered: (i) when the coating is obtained only from polymers (natural or synthetic), the advantage is the flexibility of the material, but the drawback is the lack of mechanical strength and chemical stability [53]; (ii) for coatings obtained only from inorganic materials, there is a poor adhesive strength on surfaces, film-forming ability, or the tendency to aggregate [54]; (iii) lack of stability and reduced activity under infection conditions and variable pH of different active substances can be removed by the proper use of the coating material [55]; (iv) the additives used to enhance the beneficial properties must not affect the main properties and the functionality of the primary coating material (i.e., antimicrobial) [56].…”
Section: Coating Materials For Biomedical Applicationsmentioning
confidence: 99%